New Antimicrobial and Biocompatible Implant Coating with Synergic Silver–Vancomycin Conjugate Action. Issue 6 (2nd May 2014) - Varisco, Massimo; Khanna, Nina; Brunetto, Priscilla S.; Fromm, Katharina M.
Abstract Materials foreign to the body are used ever more frequently, as increasing numbers of patients require implants. As a consequence, the numbers of implant‐related infections have grown as well, and with increasing resistance. Treatments often fail; thus, new antibacterial coating strategies are being developed by scientists to avoid, or at least strongly reduce, bacterial adhesion to implant surfaces. In this study, we focused on producing a self‐protective coating combining silver(I) ions and a vancomycin‐derived molecule, intelligent pyridinate vancomycin (IPV), with a synergetic and effective action against bacteria. These AgI–IPV conjugate‐coated surfaces are well characterized and exhibit strong bactericidal activity in vitro against Staphylococci strains. Furthermore, the released quantities of both drugs from the coated surfaces do not affect their biocompatibility and soft tissue integration. These newly developed AgI–IPV conjugate coatings thus represent a possible and efficient protection method against bacterial adhesion and biofilm formation during and after implant surgery.